Socioeconomic status correlates with clinical outcomes in patients with acral melanoma - Huang, Rong; Wang, Jiayu; Zheng, Kelin; Zhao, Mengke; Zou, Zhengyun (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to investigate the impact of socioeconomic status on survival in Chinese patients with acral melanoma.MethodsWe collected clinical and socioeconomic information of 298 primary acral melanoma patients and performed Kaplan–Meier curves, log-rank tests, Cox proportional hazards models, and Pearson’s chi-squared tests to evaluate the relationships between clinical characteristics, socioeconomic factors, and survival outcomes.ResultsAmong the clinical characteristics, age, gender, stage, Breslow thickness, and primary tumor site significantly impacted survival in acral melanoma patients (p = 0.01, p = 0.05, p < 0.01, p < 0.01, p < 0.01, respectively). Compared to individual socioeconomic factors such as education, occupation, medical insurance, and marital status, the socioeconomic level derived from these four dimensions accurately predicted patient survival. Patients with higher socioeconomic status demonstrated significantly reduced mortality risk (HR = 0.60, 95% CI = 0.40–0.91, p = 0.02). However, socioeconomic level was not found to be an independent prognostic factor for acral melanoma patients after multivariable adjustment. Notably, a negative correlation was observed between socioeconomic level and Breslow thickness.ConclusionSocioeconomic level is associated with survival in Chinese acral melanoma patients. However, this association may be attributable to Breslow thickness rather than socioeconomic status itself.